READINESS ANALYSIS OF OVO DIGITAL PAYMENT IMPLEMENTATION AT COFFEE STORE USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) METHOD ( Study Case: Kontekstual Coffee ) - Muhammad faiz rizza mubarak; Sarah Astiti S.Kom., M.MT; Resad Setyadi S.T.,S.Si.,MMSI (Soegijapranata Catholic University, 2023)
Digital payments are a new technological development as financial technology (Fintech). The purpose of this study is to analyze readiness and find out influencing factors _ the level of use of OVO as a digital payment tool in the context of coffee with use TAM variable perceived usefulness (PU) , perceived ease of use (PEU), Atittude Toward Using (ATU), Behavioral Intention (BI). The analysis model of this research uses the Technology Acceptance Model (TAM). Retrieval technique sample used is technique sample convenience. While the data obtained in the form of primary data because data collection is done with method spread online questionnaire. As much 50 results questionnaire accepted and all could processed by researchers. Data analysis is carried out with use technique analysis using statistical product and service solutions (SPSS) programs. The research results obtained is PU, PEU, and ATU have positive influence to BI, as well as PU and PEU have positive influence to ATU.